Re-engineering traditional urban water management practices with smart metering and informatics. (March 2018) - Nguyen, Khoi A.; Stewart, Rodney A.; Zhang, Hong; Sahin, Oz; Siriwardene, Nilmini
Abstract: Current practice for the design of an urban water system usually relies on various models that are often founded on a number of assumptions on how bulk water consumption is attributed to customer connections and outdated demand information that does not reflect present consumption trends; meaning infrastructure is often unnecessarily overdesigned. The recent advent of high resolution smart water meters and advanced data analytics allow for a new era of using the continuous 'big data' generated by these meter fleets to create an intelligent system for urban water management to overcome this problem. The aim of this research is to provide infrastructure planners with a detailed understanding of how granular data generated by an intelligent water management system ( Autoflow © ) can be utilised to obtain significant efficiencies throughout different stages of an urban water cycle, from supply, distribution, customer engagement, and even wastewater treatment. Highlights: Smart water metering technology. Benefits and opportunities from using smart water meters in urban water management. Intelligent system for autonomous water end-use disaggregation & demand forecasting. Intelligent system demonstrated for various urban water management practices.